Predictors of mortality in nursing home residents with advanced dementia - Hicks, Kathryn L. (2010)
This analysis uses data from the Care of Nursing Home Residents with Advanced Dementia (CareAD) study to investigate which factors increase risk of death in patients who are in the advanced stages of dementia. The hypothesis of this analysis was that specific illnesses with known high mortality would be associated with increased risk of death in the population of nursing home residents with advanced dementia, after controlling for demographic variables and disease stage variables. Baseline data on 123 end-stage dementia nursing home residents were analyzed with a Cox proportion hazards regression. Of the comboridities studied, pneumonia was the only illness significantly associated with shortened survival. This information can help healthcare professionals assist surrogate decision makers in making medical decisions regarding the treatment of co-morbid medical illness in persons with advanced dementia.